Discussion on IP Network Equipment Multi-Service Stressing Test Method - Huanan Chen; Subin Wang; Aifeng Xu (Dianxin kexue)
Referred to the development trend of the communication industry, the changes of IP network equipment testing requirements were analyzed and the limitations of the traditional testing method were explained. Through evolution of carrier's business in the future, a new method of IP network equipment business superposition test was put forward, and the core router was introduced to establish multi-service overlay test model and realization process. The multi-service stressing test case about the core router was discussed in detail. A more feasible test solution for the carrier was provided by comparing with the traditional test results at last.